WAYS TO ENSURE THE INTEGRATION OF THE BANKING SYSTEM OF UZBEKISTAN TO THE WORLD FINANCIAL SYSTEM (ResearchJet Journal of Analysis and Inventions, 2021)
The banking system of the Republic of Uzbekistan is analyzed. Practical proposals are provided to ensure the integration of the banking system of Uzbekistan into the global financial system.